Don't forget student-teacher dependency! A Meta-analysis on associations with students' school adjustment and the moderating role of student and teacher characteristics. Issue 5 (3rd September 2021) - Roorda, Debora L.; Zee, Marjolein; Koomen, Helma M. Y.
ABSTRACT: A meta-analytic approach was used to examine associations between student-teacher dependency and students' school adjustment (engagement, achievement, externalizing behavior, internalizing behavior, and prosocial behavior). Furthermore, we investigated whether associations between dependency and school adjustment were moderated by student and teacher characteristics. In total, the meta-analysis included 28 studies ( N = 7849 students) from preschool to upper elementary school. The results showed that the overall associations between dependency, on the one hand, and engagement, achievement, and prosocial behavior, on the other, were negative and small to medium, whereas associations with externalizing and internalizing behavior were positive and medium (externalizing behavior) or medium to large (internalizing behavior). As far as moderator analyses were significant, they were in line with the academic risk hypothesis (i.e., stronger associations for at-risk students).